The Influence of Quality of Work Life (QWL) and Job Satisfaction on Police Performance at the South Kalimantan Regional Police - Vita Mayastinasari; Bayu Suseno (Transpublika Publisher, 2026)
The study was set against key challenges facing Polri, including heavy workloads, organizational restructuring, and the need to balance public and internal job satisfaction which are factors affecting morale and institutional effectiveness, and highlighting QWL and job satisfaction as critical determinants of police performance. This study endeavored to delineate the interrelationship between Quality of Work Life (QWL), job satisfaction, and police performance within the South Kalimantan Regional Police. A quantitative research paradigm was employed, utilizing multiple linear regression procedures executed through SPSS software. Empirical data were elicited via structured questionnaires and subsequently subjected to psychometric validation, reliability verification, and classical assumption diagnostics, including assessments of multicollinearity, heteroscedasticity, and distributional normality. Analytical procedures comprised partial (t-test) and simultaneous (F-test) regression examinations, alongside the coefficient of determination (R²) to ascertain the magnitude of variance explicated by the predictor variables. The investigation encompassed 531 police personnel selected through a probabilistic random sampling framework, with instrument dissemination conducted through social media channels. The research steps involved collecting data from respondents through a questionnaire measured using a Likert scale ranging from 1 to 5. The data testing stages included validity and reliability tests to ensure that each questionnaire item measured the true and consistent variable, and a t-test to examine partial hypotheses. The results of this study indicate that Quality of Work Life (QWL) has a positive relationship with police performance at the South Kalimantan Regional Police, and job satisfaction has a positive relationship with police performance at the South Kalimantan Regional Police.